Acceptability of impregnated school uniforms for dengue control in Thailand: a mixed methods approach - Natasha Murray; Suphachai Jansarikij; Phanthip Olanratmanee; Pongsri Maskhao; Aurélia Souares; Annelies Wilder-Smith; Pattamaporn Kittayapong; Valérie R. Louis (Taylor & Francis Group, 2014)
Background: As current dengue control strategies have been shown to be largely ineffective in reducing dengue in school-aged children, novel approaches towards dengue control need to be studied. Insecticide-impregnated school uniforms represent an innovative approach with the theoretical potential to reduce dengue infections in school children. Objectives: This study took place in the context of a randomised control trial (RCT) to test the effectiveness of permethrin-impregnated school uniforms (ISUs) for dengue prevention in Chachoengsao Province, Thailand. The objective was to assess the acceptability of ISUs among parents, teachers, and principals of school children involved in the trial. Methodology: Quantitative and qualitative tools were used in a mixed methods approach. Class-clustered randomised samples of school children enrolled in the RCT were selected and their parents completed 321 self-administered questionnaires. Descriptive statistics and logistic regression were used to analyse the quantitative data. Focus group discussions and individual semi-structured interviews were conducted with parents, teachers, and principals. Qualitative data analysis involved content analysis with coding and thematic development. Results: The knowledge and experience of dengue was substantial. The acceptability of ISUs was high. Parents (87.3%; 95% CI 82.9-90.8) would allow their child to wear an ISU and 59.9% (95% CI 53.7-65.9) of parents would incur additional costs for an ISU over a normal uniform. This was significantly associated with the total monthly income of a household and the educational level of the respondent. Parents (62.5%; 95% CI 56.6-68.1) indicated they would be willing to recommend ISUs to other parents. Conclusions: Acceptability of the novel tool of ISUs was high as defined by the lack of concern along with the willingness to pay and recommend. Considering issues of effectiveness and scalability, assessing acceptability of ISUs over time is recommended.